The Evolution of Human Development Through the Eyes of ICT in Developing Countries Based on Panel Data from 2007 to 2017. Issue 3 (December 2022) - Mothafar, Nora A.; Zhang, Jingxiao; Al-Maqrami, Ibrahim
This paper examines the role of information communication technologies (ICT) in human development (HDI) and its three sub-dimensions in developing countries. ICT has become one of the most essential tools in the development community to enable countries to achieve specific development goals, including education, health, economic opportunities and poverty eradication. Comparing the effect of ICT on, HDI and its sub-dimensions, over the period 2007–2017 and testing the relationship between them has been done using panel data models. The results show that there was a positive correlation between ICT, HDI and its three sub-dimensions: 1% increase in IDI leads to 0.082% growth in HDI; the coefficients of income, education and health indices in developing countries are positive and statistically significant; and every 1% increase in the IDI index will drive income, education and health. The indicators increased by 0.014%, 0.029% and 1.34% respectively. This analysis suggests that ICTs promote human development in developing countries. A low's positive impact on income indices, however, is not significant for developing countries, which have high health and education indices.